2019
DOI: 10.1111/iwj.13070
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in the healing of diabetic ulcers

Abstract: MicroRNAs (miRNAs) are small protected molecules with a length of 18 to 25 nucleotides. Many studies have recently been conducted on miRNAs, illustrating their role in regulating many biological, physiological, and pathological activities, such as maintaining cellular signalling and regulating cellular pathways. The main role of miRNAs is to regulate the expression of genes after translation, which can lead to the destruction or suppression of translation by binding to mRNAs. As any change in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 171 publications
(401 reference statements)
0
19
0
2
Order By: Relevance
“…3 In recent years, an increasing number of studies have shown that abnormal expression of microRNAs (miRNAs) is closely associated with the occurrence and prognosis of DFU. 4 MiRNAs are a class of endogenous non-coding RNAs with a length of approximately 18-25 nucleotides. They can regulate the expression of a target gene by specifically binding to the 3′ untranslated region of downstream target mRNA to guide the silencing complex to degrade mRNA or…”
Section: Introductionmentioning
confidence: 99%
“…3 In recent years, an increasing number of studies have shown that abnormal expression of microRNAs (miRNAs) is closely associated with the occurrence and prognosis of DFU. 4 MiRNAs are a class of endogenous non-coding RNAs with a length of approximately 18-25 nucleotides. They can regulate the expression of a target gene by specifically binding to the 3′ untranslated region of downstream target mRNA to guide the silencing complex to degrade mRNA or…”
Section: Introductionmentioning
confidence: 99%
“… 3 A body of studies have found that the abnormal expression of miRNAs is associated with the occurrence and development of many diseases, including the healing of diabetic foot ulcers and the regulation of bone formation. 4 , 5 MiR-34c is a member of the miR-34 family and has been extensively explored in tumor formation, 6 renal fibrosis, 7 Alzheimer’s disease, 8 and so forth. Recent studies have shown 9 that miR-34c can aggravate chronic wound inflammation, inhibit the proliferation and migration of keratinocytes, promote their apoptosis, and hinder the re-epithelialization of wounds.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), endogenous small noncoding RNAs 18‐25 nucleotides long, played a significant role in the regulation of gene expression by specifically binding with the 3′‐UTR region of downstream target messenger RNA (mRNA), which results to the inhibition of mRNA translation or direct degradation of miRNA 4 . Numerous studies have established the relationship between abnormally expressed miRNAs and the occurrence and development of many diseases, including the healing process of DFU and the regulatory process of bone formation 5‐7 . Furthermore, miR‐24 was an abundantly expressed and highly conservative miRNA put together with miR‐23 and MiR‐27 on human chromosomes 9 and 19 8 .…”
Section: Introductionmentioning
confidence: 99%